Examing CSR Strategy for Financial Institutions: A Case of Acess Bank. - Talibzadeh, Jamilya (ADA University, 2015)
This Business Consultancy Project (BCP) rums to elaborate recommendations on Corporate Social Responsibility Strategy (CSR) of Access Bank. At present Access Bank is one of the leading banks in Azerbaijan and already has more than 150CSR projects in its portfolio. The bank management maintains focus on the social and environmental problems of the community and develops socially responsible products and services referring to its CSR activity as one of core values of the bank. The problem is that the first and, so far, only CSR strategy of Access Bank was developed in 2008 and does not address current needs and trends in the field of CSR and community development. The task is to define areas in which the bank can, in the most effective way, impact solutions of social problems and promote sustainable development. Empirical analysis is based on data collected from primary and secondary research. Primary research included interviews, questionnaires and surveys, while secondary research comprised information from reliable sources, such as research papers, academic articles, statistical publications, analytical reports, relevant literature and others sources, either paper based or retrieved from the Internet. The research paper gives a notion about the term CSR and briefly reviews its evolution, touching upon different approaches used by scholars over recent decades and the new idea of Creating Shared Values (CSV). Special attention is paid to CSR in the financial industry as main point of interest. The section refers to works of such well-known scholars and economists as H.Bowen, William C.Frederick, H. Gordon Fitch, M.Baker, M.Friedman, Michael E. Porter, Mark R. Kramer, T.Dyllick and others.
Keywords: Business; CSR Strategy.; Finance.; Banking.; Financial Institutions.; Acess Bank--Azerbaijan.